Telework in a pandemic context: protocol of a participatory study on the effects of teleworking conditions on the well-being and social participation of workers - Alexandra Lecours; Marie-Michèle Lord; Marie-Hélène Gilbert; Charlotte Labrecque; Frédéric Boucher (BMJ Open)
Introduction Although several authors have been interested in the well-being and social participation of teleworkers in the context of the COVID-19 pandemic, it appears that most of the recommendations issued are based on literature reviews or expert opinions; yet few authors have documented the perspectives of the workers. The aim of this study is to explore workers’ perspectives of teleworking in the context of the COVID-19 pandemic regarding the effects on their well-being and social participation.Methods and Analysis Using a participatory study protocol involving the collaboration of a community organisation defending workers’ rights, the first step will be to conduct focus groups to qualitatively describe workers’ perspectives of their teleworking conditions. Then, an online questionnaire will be administered to a large pool or workers to quantitatively explore the influence of individual, organisational and environmental variables on the well-being and social participation of workers. The thematic and statistical analyses of the data collected will indicate successful practices to be adopted by workers and organisations. These successful practices will be validated by workers through a Technique for Research of Information by Animation of a Group of Experts group and will serve as concrete tools to better support workers’ participation in teleworking.Ethics and dissemination The approval of the research ethics board of the Centre intégré universitaire de santé et de services sociaux de la Capitale Nationale has been obtained. Findings will be shared with various stakeholders including workers, employers, insurers and unions. Findings will be disseminated in webinars, peer-reviewed journals and lectures.